Comparison of preoxygenation efficiency with Intersurgical Economy and Intersurgical QuadraLite anaesthetic face masks - Sakalauskaitė, Greta; Kauzonas, Evaldas; Bukelytė, Greta; Janulevičienė, Rūta; Kontrimavičiūtė, Eglė (Acta medica Lituanica, 2019)
Background. Sufficient preoxygenation prevents arterial oxygen desaturation prior to intubation. An optimally sealed facemask is necessary for fast preoxygenation. The study was aimed at comparing the efficiency of preoxygenation using two different face masks. Materials and methods. In 2018, a prospective study was conducted. Patients were classified into two groups: group A – Intersurgical Economy face masks, group B – Intersurgical QuadraLite masks. The circuit was flushed with 100% O2 for 30s, preoxygenation started with flow of 8l/min, FiO2100. The patients were asked to breathe deeply. Fentanyl (1–2 mcg/kg) was administered to increase mask toleration. End-tidal oxygen concentration (EtO2) ≥90% was the goal. EtO2 was monitored after 30, 60, 90, 120, 180, 210, 240, 270 and 300 seconds. Data was analyzed using the Independent-Samples T-test and the Mann-Whitney-U test. Results. Twelve patients were enrolled in group A and 19 in group B. Differences in sex, age, BMI and Mallampati class in the groups were statistically insignificant (p = 0.13, 0.39, 0.65, 0.43 respectively). Patients assigned to ASA I – 25.8% (n = 8–>2/6), ASA II – 71.0% (n = 22–>10/12), ASA III – 3.2% (n = 1–>0/1), p = 0.64. The success rate of preoxygenation to EtO290 within 5 min was statistically significantly different in the groups, with 33.3% in group A and 94.7% in group B (p < 0.01). Mean time to EtO290 was 228.3 ± 104.0/164.4 ± 84.3. Mean EtO2 after: 30s – 56.0 ± 13.5/69.3 ± 11.2 (p < 0.01); 60s – 63.8 ± 15.3/76.1 ± 11.7 (p = 0.02), 90s – 67.8 ± 17.7/80.7 ± 10.1 (p = 0.03); 120s– 69.6 ± 18.2/83.4 ± 10.0 (p = 0.03), 150s–71.1 ± 19.0/87.1 ± 6.5 (p = 0.01); 180s – 72.9 ± 16.8/88.5 ± 5.3 (p = 0.01), 210s – 72.6 ± 18.0/89.2 ± 5.1 (p < 0.01); 240s – 74.17 ± 15.4/90.0 ± 4.3 (p < 0.01), 270s-76.3 ± 16.3/90.2 ± 3.6; 300s – 77.8 ± 14.6/90.2 ± 1.5 (p < 0.01). Conclusions. Preoxygenation was significantly more efficient and faster with Intersurgical QuadraLite face masks.
Keywords: preoxygenation; face mask; oxygen